Helicobacter pylori Might Induce TGF‐β1‐Mediated EMT by Means of cagE. Issue 6 (3rd March 2015) - Chang, Hyun; Kim, Nayoung; Park, Ji Hyun; Nam, Ryoung Hee; Choi, Yoon Jeong; Park, Seon Mee; Choi, Yoon Jin; Yoon, Hyuk; Shin, Cheol Min; Lee, Dong Ho
Abstract: Background: Epithelial–mesenchymal transition (EMT), in which polarized epithelial cells have mesenchymal cell phenotypes, is thought to be a key process of invasion and metastasis of cancer. Transforming growth factor beta‐1 (TGF‐β1) is known to be carcinogenic and Helicobacter pylori is a predominant carcinogen of gastric cancer. Our study aimed to determine whether TGF‐β1 or H. pylori infection enhances EMT process and cytotoxin‐associated gene E (CagE) is associated with EMT. Materials and Methods: Human gastric cancer cell AGS and MKN45 were treated with recombinant TGF‐β1 or H. pylori including cagE ‐negative (Δ cagE ) mutant. Besides the assessment of EMT‐related markers expression levels by means of RT‐qPCR, Western blot, and immunofluorescence assay, the induction of in vitro EMT on gastric cancer cells (AGS and MKN cell lines) was confirmed by wound‐healing assay and invasion assay. Results: When gastric cancer cells were treated with TGF‐β1 or various strains of cagE‐ positive H. pylori, EMT‐related marker altered significantly. However, the Δ cagE mutant did not. Wound‐healing assay and invasion assay showed enhanced migration ability of the cells treated with cagE‐ positive H. pylori but not in Δ cagE mutant. Conclusions: EMT induction in gastric cancer cells by TGF‐β1 was confirmed. Only infection with cagE ‐positive H. pylori upregulated the TGF‐β1‐mediated EMT pathway and consequently promotes EMT. Therefore, H. pylori might induce TGF‐β1‐mediated EMT associated with the cagE .